A Multidisciplinary Study on the Seismic Vulnerability of St. Agostino Church in Amatrice following the 2016 Seismic Sequence. Issue 6 (2nd July 2020) - Grazzini, Alessandro; Chiabrando, Filiberto; Foti, Sebastiano; Sammartano, Giulia; Spanò, Antonia
ABSTRACT: The big earthquake of August 24, 2016 and subsequent major shocks severely damaged many historic villages in Central Italy and dramatically showed the intrinsic vulnerability of the diffused architectural heritage. The St. Agostino church is one of the collapsed historical buildings, being inside the epicentre village of Amatrice. During the long seismic earthquake swarm, progressively the church was damaged and monitored. This multidisciplinary study of the damage of the church includes correlations of all the data derived from three steps geomatics surveys (3D aerial and terrestrial models): the archival drawings and images documenting previous events distressing the building, the previous strengthening intervention, and finally the seismic site response analysis (from Amatrice's accelerometric station). Through a back analysis carried out by a finite elements model, it was possible to understand the seismic vulnerability of this historical building, in relation to the previous interventions and damage events. The proposed methodology, based on the interdisciplinary data analysis, provides useful information for the next strengthening projects of damaged historical monument.